Effects of donor and acceptor doping on dielectric and ferroelectric properties of Ba0.7Ca0.3TiO3lead-free ceramics - Panupong Jaiban (2018)
© 2016 Elsevier B.V. (Ba 0.7 Ca 0.3 )TiO 3 , (Ba 0.7 Ca 0.3 ) 0.995 Ti 0.99 Nb 0.01 O 3 and (Ba 0.7 Ca 0.3 )Ti 0.99 Mg 0.01 O 2.99 ceramics were prepared employing a solid state sintering method. The presence of Ti 4+ and structural changes were revealed by X-ray diffraction patterns and X-ray absorption spectra. Upon substitution of Nb 5+ and Mg 2+ ions, a decrease of the ferroelectric transition temperature near room temperature and relaxor-like features of the dielectric properties were observed in correlation with decreased tetragonality. The change in phase transition temperature affected significantly piezoelectricity and ferroelectricity of doped ceramics. The doping could enhance the dielectric properties near room temperature of BCT ceramic. The results here suggest that dielectric, piezoelectric and ferroelectric properties of BCT may be largely tunable by Nb and Mg dopants, and BCT could be an alternative material for ferroelectric devices.